Risque de décrochage après une rupture de contrat d'apprentissage : l'exemple d'un CFA en Alsace - Stéphane Guillon; Stéphanie Hinsinger (Université de Provence, 2016)
The breach of contract during an apprenticeship strengthens the risk of dropout, weakens the training period and reduces chances for graduation. Nonetheless some pedagogical measures taken before and after an apprenticeship can make success possible despite the breach of contract, which most of the time is not due either to work conditions or professional tasks nor apprentices' motivation. Our paper presents some results of research made in 2014 questioning 214 apprentices who have faced a contract breach in apprenticeship between 2010 and 2013, enrolled in a training center in Alsace. We show that dropout can be avoided if the apprenticeship period had been prepared but also if the apprentice is accompanied after the breach. Both measures improve school orientation, professional relationship with the apprentice's master, make reorientation less frequent and above all enable further graduation.